Who are the Best Candidates for Decompressive Surgery and Spine Stabilization in Patients With Metastatic Spinal Cord Compression?: A New Scoring System. Issue 18 (15th September 2016) - Lei, Mingxing; Li, Jianjie; Liu, Yaosheng; Jiang, Weigang; Liu, Shubin; Zhou, Shiguo
Abstract : Study Design: A retrospective study. Objective: This study aims to develop a new scoring system that can guild surgeons to select the best candidates for decompressive surgery in patients with metastatic spinal cord compression (MSCC). Summary of Background Data: Predicting survival and functional outcome is essential when selecting the individual treatment for patients with MSCC. The criteria for identifying MSCC patients who are most likely to benefit from decompressive surgery remain unclear. Methods: We retrospectively analyzed 12 preoperative characteristics for postoperative survival in a series of 206 patients with MSCC who were operated with decompressive surgery and spine stabilization. Characteristics significantly associated with survival in the multivariate analysis were included in the scoring system. Postoperative function outcome was also analyzed on the basis of the scoring system. Results: According to the multivariate analysis, primary site ( P < 0.01), preoperative ambulatory status ( P < 0.01), visceral metastases ( P < 0.01), preoperative chemotherapy ( P = 0.02), and bone metastasis at cancer diagnosis ( P = 0.03) had a significant impact on postoperative survival and were included in the scoring system. According to the prognostic scores, which ranged from 0 to 10 points, three risk groups were designed: 0 to 2, 3 to 5, and 6 to 10 points. The corresponding 6 months survival rates were 8.2%, 56.5%, and 91.5%, respectively ( P < 0.01), and postoperative ambulatory rates were 35.7%, 73.3%, and 95.9%, respectively ( P < 0.01). Conclusion: We present a new scoring system for predicting survival and function outcome of MSCC patients after surgical decompression and spine stabilization. This new scoring system can help surgeons select the best candidates for surgical treatment. Level of Evidence: 4